"In dem auf unserem Bild sichtbaren Gebäude befindet sich das Gebietskomitee der K.P.S.U. des Urals"
"In dem auf unserem Bild sichtbaren Gebäude befindet sich das Gebietskomitee der K.P.S.U. des Urals".